AI-BASED ENTREPRENEURSHIP LEARNING, DIGITAL LITERACY, AND PROJECT-BASED LEARNING IN FORMING ENTREPRENEURIAL INTENTION: EVIDENCE FROM HIGH SCHOOL STUDENTS IN IDONESIA - Yuni Amalia Prihatin; Muh. Fahrurrozi; Huzain Jailani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The high unemployment rate among high school graduates in Indonesia demands the strengthening of digital technology-based entrepreneurship education. This explanatory quantitative research aims to analyze the effect of Artificial Intelligence (AI)-based entrepreneurship learning, digital literacy, and Project-Based Learning (PBL) on students’ entrepreneurial intentions, with digital creativity as a mediating variable and self-efficacy as a moderating variable. Quantitative data were collected through a survey questionnaire instrument on 218 students of SMAN 1 Masbagik with a purposive sampling technique, then analyzed using a Structural Equation Modeling approach based on Partial Least Squares (SEM-PLS) through SmartPLS 4 software. The results showed that digital creativity (β= 0.218 ; p= 0.016) and self-efficacy (β = 0.426 ; p = 0.000) had a significant positive effect on entrepreneurial intention. Al learning had a direct positive effect on digital creativity (β = 0.140; p = 0.006 ) and entrepreneurial intention (β = 0.129 p = 0.045 ). Digital literacy and PBL did not have a direct impact, but had a significant indirect effect through digital creativity as a full mediator. Digital creativity did not mediate Al learning, and self-efficacy did not moderate all paths. The structural model had an R² = 0.415 and Q² = 0.325. The main conclusion of this study demonstrates that students’ entrepreneurial intentions can be optimally enhanced through the integration of Al learning synergized with the development of digital creativity and strengthening students’ self-efficacy beliefs in facing the dynamics of the workplace and business opportunities in today’s rapidly evolving era of digital transformation ABSTRAK Tingginya tingkat pengangguran lulusan sekolah menengah di Indonesia menuntut adanya penguatan pendidikan kewirausahaan berbasis teknologi digital. Penelitian kuantitatif eksplanatori ini bertujuan menganalisis pengaruh pembelajaran kewirausahaan berbasis Artificial Intelligence (AI), literasi digital, dan Project-Based Learning (PBL) terhadap intensi berwirausaha siswa, dengan kreativitas digital sebagai variabel mediasi serta self-efficacy sebagai variabel moderasi. Data kuantitatif dikumpulkan melalui instrumen kuesioner survei terhadap 218 siswa SMAN 1 Masbagik dengan teknik purposive sampling, lalu dianalisis menggunakan pendekatan Structural Equation Modeling berbasis Partial Least Squares (SEM-PLS) melalui perangkat lunak SmartPLS 4. Hasil penelitian menunjukkan bahwa kreativitas digital (β=0,218; p=0,016) dan self-efficacy (β=0,426; p=0,000) berpengaruh positif signifikan terhadap intensi berwirausaha. Pembelajaran AI berpengaruh positif langsung terhadap kreativitas digital (β=0,140; p=0,006) maupun intensi berwirausaha (β=0,129; p=0,045). Literasi digital dan PBL tidak berdampak langsung, namun berpengaruh tidak langsung secara signifikan melalui kreativitas digital sebagai full mediator. Kreativitas digital tidak memediasi pembelajaran AI, serta self-efficacy tidak memoderasi seluruh jalur. Model struktural memiliki R²=0,415 dan Q²=0,325. Simpulan utama penelitian ini membuktikan bahwa intensi berwirausaha siswa dapat ditingkatkan secara optimal melalui integrasi pembelajaran AI yang disinergikan dengan pengembangan kreativitas digital serta penguatan keyakinan efikasi diri siswa dalam menghadapi dinamika dunia kerja dan peluang bisnis di era transformasi digital yang terus berkembang pesat kini